2020
DOI: 10.3390/cancers12040911
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Emerging Regulators of Signaling in the Tumor Microenvironment

Abstract: A myriad of signaling molecules in a heuristic network of the tumor microenvironment (TME) pose a challenge and an opportunity for novel therapeutic target identification in human cancers. MicroRNAs (miRs), due to their ability to affect signaling pathways at various levels, take a prominent space in the quest of novel cancer therapeutics. The role of miRs in cancer initiation, progression, as well as in chemoresistance, is being increasingly investigated. The canonical function of miRs is to target mRNAs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 141 publications
(177 reference statements)
1
16
0
Order By: Relevance
“…The group of miRNAs is a short non-coding RNA with a length of about 20–24 nucleotides and regulates nearly one-third of human genes via binding to the 3’ untranslated regions (3’ UTRs) of their target mRNAs [ 25 ]. A large number of studies have shown that miRNAs are the primary effective cargo of exosomes [ 11 , 18 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The group of miRNAs is a short non-coding RNA with a length of about 20–24 nucleotides and regulates nearly one-third of human genes via binding to the 3’ untranslated regions (3’ UTRs) of their target mRNAs [ 25 ]. A large number of studies have shown that miRNAs are the primary effective cargo of exosomes [ 11 , 18 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs that are thought to play important roles in many biological pathways 8 . Altered expression of miRNAs is involved in the regulation of crucial pathological processes in disease progression 9,10 . Exosomes are small membrane vesicles of endocytic origin that are released into the extracellular environment 11 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have been reported to participate in several malignant biological behaviours, including cell proliferation, metabolism and differentiation, at the post-transcriptional level ( 23 , 24 ). Mutations affecting miRNAs or their functional interactions with oncogenes and tumour suppressors may mediate tumourigenesis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%